PENGARUH DAYA TARIK WISATA, PERCEIVE VALUE DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI OBJEK WISATA RAWA BENTO JERNIH JAYA KABUPATEN KERINCI - Ayu Lestari, Anggia; Yuliviona, Reni; Liantifa, Melifia (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2023)
This research aims to determine the influence of tourist attractions, location and reference groups partially and simultaneously on tourists' visiting decisions at the Rawa Bento Jernih Jaya tourist attraction, Kerinci district. The sample in this study was 80 tourists from Rawa Bento Jernih Jaya, Kerinci Regency, using the Accidental Sampling method. The data analysis tool used is multiple linear regression analysis at an alpha level of 0.05. The population used in this research were tourists at the Rawa Bento tourist attraction, Kerinci Regency. This research method uses a non-probability sampling technique with an accidental sampling technique. The data obtained from the questionnaire was then processed and analyzed using multiple linear regression analysis via SPSS software. The results of the research show that there is a significant and positive influence between tourist attraction on the decision to visit the Rawa Bento tourist attraction, Kerinci Regency. There is a significant and positive influence between Perceive Value on the decision to visit the Rawa Bento tourist attraction, Kerinci Regency. There is a significant influence between the groups. Reference to the decision to revisit the Rawa Bento tourist attraction, Kerinci Regency and there is a significant and positive influence between Tourist Attraction, Perceive Value and Reference Group on the Decision to Revisit the Rawa Bento Tourist Attraction, Kerinci Regency.